An updated cost-utility model for onasemnogene abeparvovec (Zolgensma®) in spinal muscular atrophy type 1 patients and comparison with evaluation by the Institute for Clinical and Effectiveness Review (ICER) - Rebecca Dean; Ivar Jensen; Phil Cyr; Beckley Miller; Benit Maru; Douglas M. Sproule; Douglas E. Feltner; Thomas Wiesner; Daniel C. Malone; Matthias Bischof; Walter Toro; Omar Dabbous (Journal of Market Access & Health Policy)
Background: Recent cost-utility analysis (CUA) models for onasemnogene abeparvovec (Zolgensma®, formerly AVXS-101) in spinal muscular atrophy type 1 (SMA1) differ on key assumptions and results. Objective: To compare the manufacturer’s proprietary CUA model to the model published by the Institute for Clinical and Economic Review (ICER), and to update the manufacturer’s model with long-term follow-up data and some key ICER assumptions. Study design: We updated a recent CUA evaluating value for money in cost per incremental Quality-adjusted Life Year (QALY) of onasemnogene abeparvovec versus nusinersen (Spinraza®) or best supportive care (BSC) in symptomatic SMA1 patients, and compared it to the ICER model. Setting/Perspective: USA/Commercial payer Participants: Children aged <2 years with SMA1. Interventions: Onasemnogene abeparvovec, a single-dose gene replacement therapy, versus nusinersen, an antisense oligonucleotide, versus BSC. Main outcome measure: Incremental-cost effectiveness ratio and value-based price using traditional thresholds for general medicines in the US. Results: Updated survival (undiscounted) predicted by the model was 37.60 years for onasemnogene abeparvovec compared to 12.10 years for nusinersen and 7.27 years for BSC. Updated quality-adjusted survival using ICER’s utility scores and discounted at 3% were 13.33, 2.85, and 1.15 discounted QALYs for onasemnogene abeparvovec, nusinersen, and BSC, respectively. Using estimated net prices, the discounted lifetime cost/patient was $3.93 M for onasemnogene abeparvovec, $4.60 M for nusinersen, and $1.96 M for BSC. The incremental cost per QALY gained for onasemnogene abeparvovec was dominant against nusinersen and $161,648 against BSC. These results broadly align with the results of the ICER model, which predicted a cost per QALY gained of $139,000 compared with nusinersen, and $243,000 compared with BSC (assuming a placeholder price of $2 M for onasemnogene abeparvovec), differences in methodology notwithstanding. Exploratory analyses in presymptomatic patients were similar. Conclusion: This updated CUA model is similar to ICER analyses comparing onasemnogene abeparvovec with nusinersen in the symptomatic and presymptomatic SMA populations. At a list price of $2.125 M, onasemnogene abeparvovec is cost-effective compared to nusinersen for SMA1 patients treated before age 2 years. When compared to BSC, cost per QALY of onasemnogene abeparvovec is higher than commonly used thresholds for therapies in the USA ($150,000 per QALY).